"They are here to support me": Community cultural wealth assets and precollege experiences of undergraduate Black men in engineering. Issue 4 (19th August 2022) - Tolbert Smith, DeLean
Abstract: Background: Families and community networks serve as sources of cultural capital and provide resources that aid the development of Black male engineers. Community cultural wealth (CCW) has been leveraged by engineering education scholars to understand and highlight student and community assets available in communities of color. Little is known about the diverse ways that Black families support engineering education pathways. Purpose: This study characterized the diverse forms of support that Black families and extended family members provided to undergraduate Black men along their precollege engineering pathways. Method: Thirteen Black undergraduate men majoring in engineering participated in focus groups at two predominantly White institutions in different regions of the United States. Findings: The findings suggest that Black parents are engaged in the engineering learning and development of Black males, which opposes the deficit framing of Black parental engagement. The data revealed how the forms of capital overlap. A compelling finding is that capital has a bidirectional nature—meaning that participants described instances of receiving and providing capital. Conclusions: CCW framework provided a lens to explore how Black men were supported by their family networks and how they used capital to maneuver noninclusive engineering environments. The findings substantiate the role of Black parental engagement on engineering education pathways. This work promotes these parental engagement practices as worthy of inclusion in the canons of effective evidence‐based parental engagement strategies that encourage engineering learning and participation.